An assessment of furniture customization practices among selected local furniture companies - Vengco, Alexandra A.
This study intended to examine the practice of furniture customization among local furniture manufacturing companies and its perceived impact on furniture design. Using purposive sampling, ten (10) informants from ten (10) furniture companies were selected to participate in the study. The data was gathered through interviews. Instrumentation included an interview schedule and an audio recorder. Coding methods were used to analyze the data. Results showed that the informants perceived furniture customization as a process that involves designing and producing furniture pieces that are tailored to the specific needs and preferences of individual clients. Two main reasons that prompted furniture customization include the need to modify furniture sizes and the lack of choices available in retail furniture stores. Furniture customization procedures vary according to clients needs and preferences. Among its advantages include the sense of fulfillment it provides to the companies and clients, its flexibility in designing furniture, and how it leads to increased opportunities for the companies and clients. Two disadvantages in this practice involve the disagreements that may occur between clients and the company, and production limitations in customizing certain furniture designs. Furniture customization benefits and supports the local furniture industry as companies provide the market with more furniture options. The prevalent ethical issue was the copying of pre-existing designs, which was a common request received by the companies.